2020
DOI: 10.1096/fj.201902551r
|View full text |Cite
|
Sign up to set email alerts
|

Nuciferine prevents bone loss by disrupting multinucleated osteoclast formation and promoting type H vessel formation

Abstract: Recently, type H vessels were reported to couple angiogenesis and osteogenesis during osteoclastogenesis, and tartrate‐resistant acid phosphatase (Trap)+ preosteoclasts were found to secrete increased PDGF‐BB to promote type H vessel formation. Therefore, utilization of type H vessels may be a strategy to treat diseases involving bone loss. In the present study, we found that nuciferine, a natural bioactive compound, has various effects, including inhibiting osteoclastogenesis and promoting type H vessel forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Huang et al [ 25 ] reported that Harmine inhibited RANKL‐induced multinucleated osteoclast formation and alleviated bone resorption while inducing type H vessel formation. Likewise, Song et al [ 26 ] reported that Nuciferine suppressed the formation of RANKL‐induced multinucleated osteoclasts by inhibiting mitogen‐activated protein kinase (MAPK) and nuclear factor‐𝜅B (NF‐𝜅B) signaling pathways, preventing the production of multinucleated osteoclasts and increasing type H vessel formation. Intriguingly, DFO inhibits osteoclastogenesis by upregulating HO‐1 via the p38 MAPK signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al [ 25 ] reported that Harmine inhibited RANKL‐induced multinucleated osteoclast formation and alleviated bone resorption while inducing type H vessel formation. Likewise, Song et al [ 26 ] reported that Nuciferine suppressed the formation of RANKL‐induced multinucleated osteoclasts by inhibiting mitogen‐activated protein kinase (MAPK) and nuclear factor‐𝜅B (NF‐𝜅B) signaling pathways, preventing the production of multinucleated osteoclasts and increasing type H vessel formation. Intriguingly, DFO inhibits osteoclastogenesis by upregulating HO‐1 via the p38 MAPK signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Mononuclear preosteoclasts can promote the growth of type H vessels by releasing platelet-derived growth factor-BB (PDGF-BB) prior to multinucleated osteoclast formation ( Xiaoqun Li et al, 2020 ). Moreover, the number of type H vessels decreases with age to a degree consistent with the severity of bone loss ( Song et al, 2020 ). Therefore, by simultaneously interrupting the maturation and activation of osteoclasts, inhibiting bone resorption and promoting the formation of type H blood vessels, osteoporosis can be effectively prevented.…”
Section: Introductionmentioning
confidence: 96%
“…Recent studies revealed that the number of type-H vessels is apparently reduced in osteoporotic and aged bones, accompanied by a decrease in the number of osteoprogenitors [ 7 , 8 ]. Medications stimulating the formation of type-H vessels have been discovered to prevent bone loss to some extent [ 9 , 10 ]. In combination with these breakthroughs, we aim to develop a bone-targeting therapy for osteoporosis, which can inhibit bone resorption while promoting bone formation and vascularization.…”
Section: Introductionmentioning
confidence: 99%